American gods - Gaiman, Neil (New York, N.Y. : HarperTorch, 2002)
Shadow is a man with a past. But now he wants nothing more than to live a quiet life with his wife and stay out of trouble. Until he learns that she's been killed in a terrible accident. Flying home for the funeral, as a violent storm rocks the plane, a strange man in the seat next to him introduces himself. The man calls himself Mr. Wednesday, and he knows more about Shadow than is possible. He warns Shadow that a far bigger storm is coming. And from that moment on, nothing will ever he the same.
Originally published : New York : W. Morrow, 2001.
Keywords: National characteristics, American -- Fiction; Spiritual warfare -- Fiction; Ex-convicts -- fiction; Bodyguards -- Fiction; Widowers -- fiction